2018
DOI: 10.1002/anie.201810124
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Baeyer–Villiger Oxidation Catalyzed by a Flavin‐Containing Enzyme Mimic in Water

Abstract: Direct incorporation of molecular oxygen into small organic molecules has attracted mucha ttention for the development of new environmentally friendly oxidation processes. In line with this approach,b ioinspired systems mimicking enzyme activities are of particular interest since they may perform catalysis in aqueous media. Demonstrated herein is the incorporation of an atural flavin cofactor (FMN) into the specific microenvironment of aw ater-soluble polymer which allows the efficient reduction of the FMN by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…According to the previous studies,the dark reaction with H 2 O 2 leads to neutral complex [1a+ H,2 O]. [4,9] To probe if we could detect this complex, we have prepared ac hargetagged flavinium ion 1b 2+ (Supporting Information, Figure S1). [12] Ther emote imidazolium group keeps the intermediates cationic,e ven when the flavinium reaction site is neutralised.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous studies,the dark reaction with H 2 O 2 leads to neutral complex [1a+ H,2 O]. [4,9] To probe if we could detect this complex, we have prepared ac hargetagged flavinium ion 1b 2+ (Supporting Information, Figure S1). [12] Ther emote imidazolium group keeps the intermediates cationic,e ven when the flavinium reaction site is neutralised.…”
Section: Resultsmentioning
confidence: 99%
“…[3] Thec hemoselectivity of hydroperoxyflavins prompted their development as oxidants in organic synthesis. [4] Recently,researchers shifted their focus towards flavin-photocatalysed oxidation reactions and developed procedures for photooxidation of substituted toluenes,benzyl alcohols and benzaldehydes using O 2 as the terminal oxidant. [5,6] Them echanism of the flavin derivative catalysed photooxidation of benzyl-alcohols has been thoroughly studied by femtosecond transient absorption measurements (UV/Vis) [7] and by NMR.…”
Section: Introductionmentioning
confidence: 99%
“…The efficient artificial flavoenzyme thus created allows NADH oxidation by the FMN incorporated cofactor to proceed with a 200‐fold rate enhancement. This reactivity was demonstrated in oxidation of thioanisole with dioxygen as oxidant and further studies enlarged the reaction scope of this synzyme towards Baeyer‐Villiger monooxygenases (BVMOs) …”
Section: Combined Flavin/nad(p)h Manifoldsmentioning
confidence: 85%
“…This reactivity was demonstrated in oxidation of thioanisole with dioxygen as oxidant and further studies enlarged the reaction scope of this synzyme towards Baeyer-Villiger monooxygenases (BVMOs). [69] Combination of transition metal-based systems with both flavin and NADH has been reported with a proflavin system used as photosensitized and coupled to the regeneration of NADH from NAD + . The electron flow resulting from the reduction of the photosensitizers was transferred to the NAD + / NADH cycle by a rhodium-based complex and results in the final reduction of α-ketoglutarate into L-glutamate (Scheme 10).…”
Section: Combined Flavin/nad(p)h Manifoldsmentioning
confidence: 99%
“…[32] Finally we demonstrated that the reduced, artificial flavoenzyme could also directly activate molecular dioxygen under aerobic conditions and catalyzed at room temperature in water the Baeyer-Villiger reaction. [33] This afforded a new environmentally friendly oxidation process for the direct incorporation of an oxygen atom into small organic molecules.…”
Section: Reductive Activation Of O2 In the Presence Of Artificial Redmentioning
confidence: 99%